Clinicopathological profile of ameloblastoma: A retrospective study for 5-years - Zavita Anwar, Zavita (Universidad Tecnica de Manabi, 2022)
Abstract---The emergence of ameloblastoma as the second most common odontogenic tumor that occurred after odontomas is a rare capacity to metastasize. Furthermore, this study aims to determine the clinicopathological profile of ameloblastoma. This was a descriptive retrospective study. The samples were obtained from histopathological examination data from the patients with ameloblastoma from January 2016 to December 2020 at the Anatomical Pathology Laboratory of Dr. Soetomo Academic General Hospital Surabaya. Moreover, the diagnosis of confirmed ameloblastoma was obtained in 95 cases. The occurrence age of ameloblastoma in both jaws ranged from 7-84 years with a mean age of 36.3 years. In this case, the highest number of patients with ameloblastoma has occurred in the 41-50 years age group with 21 cases (22%). There was no gender predilection in ameloblastoma. The most common location of ameloblastoma was found in the mandible which was confirmed in 82 cases (86%) and found in the maxilla for 13 cases (14%). In all, the most common type of ameloblastoma found was solid/multicystic ameloblastoma in 88 cases (93%) and unicystic ameloblastoma in 7 cases (7%). In the extent of solid or multicystic ameloblastoma, the most common mixed type was confirmed in 41 cases (43%) and the most diverse incidence being plexiform and follicular types. These data are expected to serve as baseline information on the occurrence of various histopathological types of ameloblastoma at the Anatomical Pathology Laboratory of Dr. Soetomo Academic General Hospital. Furthermore, these are expected as a basis for future epidemiological data as well.